(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2010)
With the Internet so easily available nowadays, I decided (just for the fun of it but also out of curiosity) to do a Google search to see how many entries I could find for “heritage and history”. In a split second no fewer than 840 000 results appeared. I felt exhausted even before I even started surveying the results. This gives a sense of how history educators must sometimes feel when they have to teach content or facilitate, but still have to find the time on a daily or weekly basis to engage with meaningful ideas and activities as part of the History curriculum. This is especially true for heritage assignments that from 2012 will, among others, be the focus in the Grade 10 History curriculum. In September 2010 the South African Society for History Teaching held its second conference since its founding on the theme of heritage and its inevitable associations with history. As I do not wish to repeat here the theories and practical suggestions1 which other educators of history with expertise in heritage have recently developed, my focus is more practical. It is practical in the sense that it will motivate educators to use existing content in local histories and local heritage within history curricula frameworks (in all educational phases) to serve as examples of broader trends – apart from this, heritage is also to be appreciated for its own sake as well as acting as a micro anchor and milestone from which broader historical developments evolve. In this regard my focus therefore was more on identifying historical content in past debates and research deliberations with the intention to support educators with content that they can explore inside and outside the formal classroom set-up. Therefore the discussion merely: • Gives glimpses of local history and heritage in the writing of historians and others; • Deals with one local heritage example in the classroom (to connect with the SASHT 2010 conference theme: The “how to of yours, mine and ours in a still divided community; environment”),namely the 2010 Shaka statue debacle; • Gives some concluding suggestions on heritage, history and the History curriculum.